Comparative radiological study of cardiac parameters between lined up and rotated dorsoventral view of the thorax - Baldi Aste, Bianca M. (2020)
The aim of this study was to compare the cardiac parameters of chest X-rays with aligned dorsoventral view with those of the rotated dorsoventral view of the same patient to determine the acceptable degree of rotation for these views. Fifty-three rotated dorsoventral plates from 32 canine patients were used and the parameters compared of those plates with their respective control samples or aligned dorsoventral plates. To do this, the clockface analogy test and the cardio-thoracic ratio were used and complemented with their respective right side-lateral view, allowing obtaining the angle of rotation. The results of the rotated samples were assigned to a group of 0.1º to 6º of rotation and to another group of 6º to 12º of rotation. Each cardiac chamber was evaluated with its respective control plate by the McNemar test. The group from 0.1º to 6º rotation presented a probability value of 0.1025 when evaluating the right atrium, 0.6547 for the left atrium, 0.1573 for the right ventricle and 0.3173 for the left ventricle, being valid for diagnosis; unlike the group of 6° to 12° rotation that obtained 0.0196 for the right atrium, 0.0578 for the left atrium, 0.0114 for the right ventricle and 0.0126 for the left ventricle, not being acceptable for diagnosis.